Influence of full-spectrum lighting on blood pressure, heart rate and visual comfort on young adults. Issue 4 (April 2021) - Tang, Luyao; Chen, Shaofan; Liu, Muqing; Su, Chengyue
This study examined the effects of lighting with different spectra on humans, as measured by mean arterial pressure, heart rate and visual comfort. Twenty subjects were recruited and tested under 12 different lighting spectra, produced by self-made luminaires respectively. In order to evaluate the shape similarity between the measured spectrum and the solar spectrum, a full-spectrum index E (0–100) was proposed. The higher the value of E, the closer the spectrum is to the full range of daylight. Groups whose E value is above 90 are classified as full-spectrum lighting groups. Subjects were required to maintain a calm mood during the 3-h testing time, and data were recorded every 20 min. Pearson correlation test and independent samples t-test were performed on the mean values. Results showed that heart rate and visual comfort were likely to be influenced by the spectrum. The higher the E is, the lower the average heart rate is and the higher the visual comfort is. Full-spectrum lighting group has a significantly lower heart rate and higher visual comfort than the control group.